Communicative Provocation Coming from Aggressive Bloggers and Improvement of Professional Performance of Traffic Patrol Officers of the State Inspectorate for Road Traffic Safety - Borisova, S.E.; Zeynalov, F.N. (Psihologiâ i pravo, 2020)
This study clarifies the essence of communicative provocation with elements of verbal aggression manifesting in the way internet bloggers behave if conflict situations arise between them and traffic patrol officers of the State Inspectorate for Road Traffic Safety. The specifics of communicative provocation is analyzed from the psychological and legal perspective and on the basis of video recordings of direct communication between road users and traffic patrol officers. We describe the tactics of bloggers' conflict verbal behavior and also the psychological makeup of traffic patrol officers as the target of communicative provocation. Suggestions of psychological and legal significance are formulated with the view of: 1) relaxing the conflict potential of the situations under consideration; 2) strengthening the skills of traffic patrol officers of the State Inspectorate for Road Traffic Safety; 3) improvement of their professional performance. Раскрывается смысл коммуникативной провокации с элементами речевой агрессии, проявляющейся в поведении блогеров в конфликтных ситуациях взаимоотношений с сотрудниками дорожно-патрульной службы Государственной инспекции безопасности дорожного движения. Специфика коммуникативной провокации анализируется с психологической и правовой точек зрения, исходя из содержания видеозаписей непосредственного общения участников дорожного движения и сотрудников Госавтоинспекции. Характеризуются тактики конфликтогенного речевого поведения блогеров, а также психологические особенности сотрудников дорожно-патрульной службы Государственной инспекции безопасности дорожного движения как объекта коммуникативной провокации. Формулируются предложения психолого-правового значения, направленные на ослабление степени конфликтности рассматриваемых ситуаций, повышение уровня компетентности сотрудников дорожно-патрульной службы Государственной инспекции безопасности дорожного движения и совершенствование их профессиональных действий.